"Your Kitchen" web application - Jiang, Kailin (Nanyang Technological University, 2020)
Even before the COVID-19 began making headlines around the world, online food delivery was benefiting from broader digitization and more delivery applications. E-commerce, the general trend towards increasing urban life and changing social behaviour has been contributing to this growing sector.